Intensity and inhalation of smoking in the aetiology of laryngeal cancer - Ramroth, Heribert; Dietz, Andreas; Becher, Heiko (International journal of environmental research and public health, 2011)
The carcinogenic effect of smoking on laryngeal cancer is well established; however, the risk pattern for detailed smoking characteristics is less clear. Thus, the aim of this analysis was to quantify the impact of different inhalation behaviours on the risk of laryngeal cancer. We conducted a population-based case control study in Germany, frequency-matched for sex and age, using a standardized questionnaire covering lifelong smoking details, including age at start, time since quitting, types of smoking products, duration, intensity and inhalation behaviour. We found higher risks for increasing duration and intensity of smoking. A clear dose-response relationship was found in all inhalation subgroups, i.e., not only for deep inhalers, but also for those puffing on a cigarette. Clearly reduced risks could be observed for quitting smoking. Changing inhalation habits might be considered as a first step to reducing the risk of developing laryngeal cancer. However, the best way to effectively reduce laryngeal cancer risk is to quit smoking.
Gesehen am 09.09.2022